PERBEDAAN PENGETAHUAN DAN SIKAP GIZI SETELAH DIBERIKAN EDUKASI MP-ASI PADA IBU BAYI USIA 6-23 BULAN DI BOJONEGORO - Desiana Firdaus; Sudalhar Sudalhar; Della Riski Ananda (Jurnal Manajemen Kesehatan Indonesia, 2026)
Toddlers or infants under two years old in particular often experience malnutrition problems. This is due to inappropriate parenting patterns where one indicator is the practice of providing complementary foods that is not optimal. The purpose of this study was to examine the effectiveness of providing nutrition education on changes in maternal nutritional knowledge and attitudes regarding the provision of MP-ASI. This study included an experimental study with a pre-experimental one group pretest posttest design. The sample of this study was 28 mothers of infants aged 6-23 months. The intervention group will be given an educational intervention for 3 weeks consisting of 3 times of nutrition education. Measurements were made of maternal knowledge and attitudes regarding MP-ASI before and after being given MP-ASI. Data analysis used the Wilcoxon difference test. There was no significant difference in maternal nutritional knowledge scores before and after being given nutrition education p = 0.051 (p> 0.05). There is a statistically significant difference in the nutritional attitude scores of mothers before and after being given nutritional education with a p-value of 0.01 (p < 0.05). Nutrition education using lecture methods, interactive discussions with video media and leaflets can improve mothers' nutritional attitudes about MP-ASI. Keywords: nutrition education, knowledge, attitude